Two new species of Diarthrodes (Copepoda: Harpacticoida: Dactylopusiidae) from the Caribbean coast of Colombia - Eduardo Suárez-Morales; Juan M. Fuentes-Reinés (Revista Mexicana de Biodiversidad)
Biological samples obtained from a coastal system of northern Colombia yielded the first record of the harpacticoid copepod genus Diarthrodes Thomson, 1883 for Colombia by the presence of 2 new species. We describe the new species based on male and female specimens. Diarthrodes bodini sp. nov., a member of group I (sensu Gómez et al., 2008), appears to be most closely related to D. latisetosus Chislenko, 1978 but differs in the ornamentation of the urosomites, the length/width ratio of the P1 ENP, the relative length of the inner spine of P1 ENP1, the relative length of P3 and P4 ENP, details of the female P5 armature and seminal receptacle, and details of the male P2ENP2 and antennule segmentation. The second species, D. gomezi sp. nov. belongs to group IV; it is unique among related congeners in possessing 7 setal elements on P3-P4EXP3. It resembles D. minutus (Claus, 1863) but diverges in the relative length of the inner seta of P1ENP1, the armature of the female P1EXP2 and P5, the structure of the modified male P2ENP2, and the armature of the male P5EXP. These 2 new species represent the first records of the genus from Colombia and the second and third species known from the Caribbean. The number of species in the genus is now 45.